The Implementation of School Literacy Movement to Literate Students in Dharma Putra Elementary School at Tangerang - Vistari, Lalita; Sitinjak, Shenny Ayunuri Beata (Empiricism Journal, 2024)
This study evaluates the implementation of the School Literacy Movement (Gerakan Literasi Sekolah/GLS) at Dharma Putra Elementary School in Tangerang, Indonesia, within the framework of the Merdeka Belajar-Kampus Merdeka (MBKM) policy. The research aimed to assess the effectiveness of GLS in enhancing literacy skills, specifically focusing on student engagement and reading comprehension. A qualitative approach was employed, utilizing observations and semi-structured interviews with teachers and parents conducted from July to December 2023. Data were analyzed using a goal-oriented evaluation model and researchers classified the data into two items such as the interaction between student literacy activities and teacher involvement. The findings revealed that GLS positively impacted students on students’ engagement and reading comprehension. This research also identified gaps in parental involvement and the availability of diverse reading resources, suggesting that future GLS improvements should incorporate technological resources, expand reading materials, and foster stronger school-parent collaboration. Recommendations for addressing these challenges include the integration of e-books, more interactive reading tools, and targeted support for disengaged students. This study contributes to the literature on literacy programs by providing insights into the adaptability of GLS within the MBKM framework and proposing solutions to common literacy challenges in elementary schools.